#cyprus #coffee: Trends in the linguistic communication of young Cypriots as reflected in coffee ads on Instagram - Papadima, Aspasia (My University, 2023)
The contemporary face of Cyprus is emerging through a rapid course of changes that reflect its multicultural diversity and affect, among other matters, the use and evolution of language. Language communication seems to be adapting flexibly while trying to balance its cultural specificity with extroversion, global trends, and new forms of linguistic expression. The linguistic distinctiveness of Cyprus results from the fact that two linguistic varieties—Greek-Cypriot dialect (henceforth GCD), the oral mother tongue of Greek-Cypriots, and Common Modern Greek (henceforth Koiné), the official language of the State—are equally dominant. In recent years, GCD is being used more frequently, even in circumstances previously considered as inappropriate (such as in public speeches, broadcasted discussions and political debates, advertising, etc.), both in spoken and written communication. At the same time, the increasing spread and impact of English as a code of communication among young Cypriots is a notable phenomenon that arises from contemporary global linguistic trends, while echoing Cyprus' colonial past. Coffee tradition is considered a cultural asset in Cypriot society and requires lingering time for both the preparation and the consumption of coffee. However, modern lifestyle, socio-economic conditions as well as imported trends require new ways of approaching both the product and its promotion. Aiming at younger audiences, low-budget canned coffee has gained a noteworthy place in the market and seems to be quite popular with younger groups of Cypriots. Focusing on Mr. Brown canned coffee as a case study in coffee advertising promotion on Instagram, while drawing references from sociolinguistics and advertising theories, with the aid of semiotic analysis as a tool of interpretation and meaning, this study aims to: a) document the ways in which GCD is used in the promotion of a specific brand on Instagram, b) pinpoint the current linguistic trends and codes among youth in Cyprus as projected in multimodal advertising messages, and c) highlight the cultural meaning of specific language choices as well as the influence of globalization on local culture and language.
Keywords: Greek-Cypriot dialect; Typographic rendering; Cyprenglish; Code-switching; Code-mixing; Multimodality; Coffee advertisements; Instagram promotion